2017
DOI: 10.1089/omi.2017.0116
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Fibroblast Growth Factor 12 Gene as a Novel Potential Biomarker in Esophageal Cancer Using Cancer Genomic Datasets

Abstract: Esophageal squamous cell carcinoma (ESCC) has a complex, multifactorial etiology in which environmental, geographical, and genetic factors play major roles. It is the second most common cancer among men and the fourth most common among women in India, with a particularly high prevalence in Northeast India. In this study, an integrative in silico [DAVID, NCG5.0, Oncomine, Cancer Cell Line Encyclopedia, and The Cancer Genome Atlas (TCGA)] approach was used to identify the potential biomarkers by using the availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Our study has confirmed this type of the FGF12 epigenetic changes in prostate cancer [18]. It is revealed as a putative biomarker in esophageal cancer [25]. The ALDH1L1 gene encodes the aldehyde dehydrogenase 1 family member L1.…”
Section: Resultssupporting
confidence: 77%
“…Our study has confirmed this type of the FGF12 epigenetic changes in prostate cancer [18]. It is revealed as a putative biomarker in esophageal cancer [25]. The ALDH1L1 gene encodes the aldehyde dehydrogenase 1 family member L1.…”
Section: Resultssupporting
confidence: 77%
“…614 FGF12 gene was overexpressed in esophageal squamous cells. 615 FGF13 was highly upregulated in aggressively metastatic breast tumors and pancreatic endocrine tumors. 616 FGF14 was preferentially methylated in colorectal cancer.…”
Section: Fgf Signaling In Tumorsmentioning
confidence: 97%
“…In addition to KMT2B , we also found several other gene candidates on HBV‐related GC for further studies. TUBB2B and FGF12 have been suggested to play vital functions in prostate cancer ( Liotti et al., 2021 ), neuroblastoma ( Zafar et al., 2021 ), and esophageal squamous cell carcinoma ( Bhushan et al., 2017 ); however, their roles in HBV-related GC development have never been documented and merit further investigations.…”
Section: Discussionmentioning
confidence: 99%